2017
DOI: 10.2147/ppa.s127407
|View full text |Cite
|
Sign up to set email alerts
|

Selected factors affecting adherence in the pharmacological treatment of arterial hypertension

Abstract: BackgroundLow adherence to hypertension (HT) management is one of the major contributors to poor blood pressure (BP) control. Approximately 40%–60% of patients with HT do not follow the prescribed treatment. The aim of the study was to analyze the relationship between selected variables and adherence to hypotensive pharmacological treatment. Besides socioclinical variables, the study focused on the role of illness acceptance.Participants and methodsThe study included 602 patients with HT. Adherence and accepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 39 publications
(61 reference statements)
6
46
1
12
Order By: Relevance
“…In contrast, some researchers have also found better adherence among older patients, 23 in which patients in the age group of >40 but not > 60 and >65 were more adherent than younger age patients. 23,24 The better adherence to treatment found in elderly patients has been explained by the presence of co-morbidities, which make the patients perceive themselves as very ill and take the prescribed treatment seriously, and elderly patients in the study area might have received better care by their caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some researchers have also found better adherence among older patients, 23 in which patients in the age group of >40 but not > 60 and >65 were more adherent than younger age patients. 23,24 The better adherence to treatment found in elderly patients has been explained by the presence of co-morbidities, which make the patients perceive themselves as very ill and take the prescribed treatment seriously, and elderly patients in the study area might have received better care by their caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Sociodemographic characteristics like some age groups (younger than 65 years and older than 84 years) [53][54][55], not being partnered or married [56] or not having support in drug handling [47] and female sex [57] were related to nonadherence. Similarly, different levels of education (low as well as high levels of education) [58,59], poor numeracy [60] and low health literacy [15] were associated with nonadherence. Moreover, unemployment [31] and the income of the patient (low-class and middle-class income) [61,62] affected adherence negatively along with a busy lifestyle [28] and the use of alcohol [31] or illicit drugs [63].…”
Section: Patient Characteristicsmentioning
confidence: 96%
“…These results are consistent with previous reports. 6,3336 Furthermore, sex-race stratification revealed that the associations between comorbidities and low antihypertensive medication adherence, and shorter hypertension duration and antihypertensive medication adherence found among all women were driven primarily by white women. While neither number of comorbidities nor duration of hypertension is “modifiable” in the context of a healthcare encounter, considering these risk factors may help providers to identify patients at risk for low antihypertensive medication adherence.…”
Section: Discussionmentioning
confidence: 98%